Harnessing of the axial kinetic electron energy of a large-orbit gyrotron by an assistant azimuthal background magnetic field - Muralidhar Y.; Jain P.K.; Basu B.N. (My University, 2025)
A new method of providing a background magnetic field was proposed for a large-orbit gyrotron in a coaxial waveguide for an improvement in the device performance with respect to the gain and efficiency. The method, which consists in providing an assistant azimuthal magnetic field, over and above the conventional DC axial background field, was studied, using a kinetic theory. The method was compared with an earlier method of providing a DC radial background electrical field. The adjustment of the background fields and that of the DC kinetic energy distribution between the axial and transverse electron velocities of the beam provided a simultaneous increase in the gain and efficiency of the device. This may be attributed to the axial beam kinetic energy being harnessed by the method. © 2001 Taylor & Francis Group, LLC.